1999
DOI: 10.1021/jo990282p
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perfluoroacyl Olefinations of Aldehydes Using β-Thio-Substituted Perfluoroalkyl Enol Ethers

Abstract: α-(Methylthio)- or α-(phenylthio)-substituted perfluoroacylolefinations of nonenolizable aldehydes using the β-lithio-β-thio-perfluoroalkyl enol ethers 1 − 4 stereoselectively proceeded to give (Z)-α,β-unsaturated perfluoroalkyl ketones 9a − e, 10a − c, 11a − c, and 12a. The α-(thio)-α,β-unsaturated trifluoromethyl ketones were easily converted to 3-(thio)-2-(trifluoromethyl)-1,3-butadienes 21a − c and 22a,b in moderate to high yields (41−85%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Thin-layer chromatography showed that the starting material had disappeared. The reaction mixture was poured into diethyl ether (40 mL), washed with water (3 × 10 mL), and dried over MgSO 4 . Evaporation of the solvent gave a residue, which was purified by column chromatography, eluting with petroleum ether (60-90…”
Section: General Procedures For the Preparation Of Functionalized Polymentioning
confidence: 99%
See 1 more Smart Citation
“…Thin-layer chromatography showed that the starting material had disappeared. The reaction mixture was poured into diethyl ether (40 mL), washed with water (3 × 10 mL), and dried over MgSO 4 . Evaporation of the solvent gave a residue, which was purified by column chromatography, eluting with petroleum ether (60-90…”
Section: General Procedures For the Preparation Of Functionalized Polymentioning
confidence: 99%
“…They are useful intermediates in cycloaddition reactions and Michael-type conjugated additions, and can undergo many synthetic transformations [2], particularly in the synthesis of some natural products [3]. Recently, much attention has been paid to the fluorinated species because they can be employed as useful intermediates for the synthesis of biologically active compounds [4]. Several methods for the synthesis of functionalized trifluoromethyl 1,3-dienes have been reported [5], but they are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we investigated the syntheses and reactions of alkoxyalkenes bearing some useful substituents such asorganosulfanyl, organoselanyl,3 and perfluoroalkyl groups 45. The alkoxy alkenes that have an enol structure, which can easily undergo hydrolysis to give the alkyl ketone derivatives, and the halogen‐substituted alkoxy alkenes prepared by our original methods would both be expected to be novel precursors for aryl chloromethyl ketones and a prodrug in the treatment of Alzheimer's disease (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…
Four-carbon homologation is one of the important processes in the syntheses of the polyene antibiotics and pheromones and other bioactive compounds.1-3) The most useful reagents are the triethyl phosphonoesters (HornerWadsworth-Emmons reagents) or the Wittig type reagents, which directly react with the aldehydes and ketones to give the penta-2,4-dienals.4-7) 4-Alkoxybuta-1,3-dienyl lithiums as the other useful reagents have been reported by Wollenberg or Duhamel to easily utilize the four-carbon homologation using 4-alkoxybuta-1,3-dienyl tributyltin, [8][9][10] chloride and bromides; 11) however, more functionalized 4-alkoxybuta-1,3-dienyl lithiums have been hitherto unknown.12) Recently, we reported the two-carbon homologations such as the asulfenyl 13,14) or a-selenenyl 15) formylation of aldehydes and ketones using b-alkoxyalkenyl lithiums. Next our attention has been focused on the four-carbon homologation of the carbonyl compounds.
…”
mentioning
confidence: 99%
“…12) Recently, we reported the two-carbon homologations such as the asulfenyl 13,14) or a-selenenyl 15) formylation of aldehydes and ketones using b-alkoxyalkenyl lithiums. Next our attention has been focused on the four-carbon homologation of the carbonyl compounds.…”
mentioning
confidence: 99%